To Find Frequency of Large Fibre Sensory Neuropathy in Diabetes Mellitus and to Compare Hand Grip Strength in patients of DM with and without Large Fibre Sensory Neuropathy - Sohail Bashir Sulehria, Safi Ullah, Nasir Hussain, Asmat Ullah, Haseeb Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find frequency of large fiber sensory neuropathy in diabetes mellitus and to compare hand grip strength in patients of diabetes mellitus with and without large fiber sensory neuropathy Study setting: The study was conducted at Department of Medicine/ Diabetic Foot Care Clinic, Mayo Hospital, Lahore. Duration of study: August 25, 2020 to February 25, 2021 Study design: Cross-sectional study Methods: Total 100 patients with diabetes were enrolled. Patients had their handgrip checked. Handgrip strength of each participant was tested in morning after routine breakfast, with the help of Jammar hand dynamometer. Three readings were taken for each patient with dominant hand and average of these three was calculated for final analysis. Large fiber sensory neuropathy was assessed as per operational definition. Data were entered and analyzed by SPSS v25.0. Peripheral neuropathy was tested by Chi Square test. Data were stratified for age, gender, duration of DM and BMI. Hand grip was compared between groups by t-test. A p-value of ≤0.05 was taken as significant. Results: In this study, 100 patients presenting with diabetes mellitus were enrolled. Among these patients, 68(68.0%) were males, while 32(32.0%) were females. Age range in this study was from 18 to 60 years with mean age of 42.8±11.6 year. Frequency of large fiber sensory neuropathy was 42(42.0%) among cases presenting diabetes mellitus. Mean handgrip strength in patients with large fiber sensory neuropathy was 20.71±2.39 kg and 28.10±5.18 kg among cases without large fiber sensory neuropathy with p-value as 0.0001, which is statistically significant. Conclusion: Long-standing large fiber sensory neuropathy with type-II diabetes mellitus seems to result in a decrease in hand grip strength. This physical limitation may contribute to low productivity in people with large fiber sensory neuropathy among type-II diabetes mellitus. Keywords: Hand Grip Strength, Type-2 Diabetes Mellitus, Large Fiber Sensory Neuropathy.